Gas flow field with obstacles for PEM fuel cells at different operating conditions. (9th February 2015) - Bilgili, Muhittin; Bosomoiu, Magdalena; Tsotridis, Georgios
Abstract In proton exchange membrane fuel cells (PEMFCs) laminar flow inside anode and cathode gas channels can be disrupted by using obstacles. By arranging these obstacles near to the exit of the gas channels concentration losses due to hydrogen and oxygen consumption inside the channel will be decreased. Using a three dimensional computational model, numerical simulations are performed to investigate performance of PEMFCs containing obstacles in the anode and cathode gas flow channels. These simulations were conducted at different operating conditions (stoichiometry, relative humidity and temperature) to clarify the effects of the obstacles at specified conditions. The simulations show that the obstacles inside the gas flow channels improve the concentration distribution along the channels and the transport of the reactant gases through the gas diffusion layer (GDL). As a result, the electrochemical reaction is improved and higher cell voltage is obtained at high current densities.